Crescent-shaped dipole antenna for ultrawideband applications - Singhal S.; Singh A.K. (My University, 2025)
A crescent-shaped dipole antenna for ultrawideband applications is designed in this article. The impedance bandwidth of the designed antenna has been enhanced using modified shape of both radiator and feedline. The designed antenna provided an impedance bandwidth of 3.26-19.10 GHz (142%). It has nearly omnidirectional radiation patterns in one plane. The overall dimensions of the designed antenna are 34 × 41 mm2. The experimental and simulation results are found to be in good agreement. A comparison between the antenna performance for three different shapes of the radiator, that is, triangular, rectangular, and elliptical is also presented. The effects of three different substrate materials, that is, FR-4 epoxy, Carbon Nano Tubes, and Ni0.2Co0.2Zn0.6Fe2O4, on the designed antenna performance are also analyzed. The designed antenna has advantages of wider bandwidth and smaller dimensions over the dipole structures already reported in the literature. © 2015 Wiley Periodicals, Inc.